Penerapan Model Pembelajaran Reciprocal Teaching untuk Meningkatkan Hasil Belajar Kognitif Siswa dalam Mata Pelajaran Biologi - Hasanah, Marlia (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to improve students' cognitive learning outcomes through the application of the Reciprocal Teaching Learning Model to class XI students of SMAN 5 Palangka Raya in the 2024/2025 academic year in Biology. This research is a Classroom Action Research (CAR). This research was conducted in 2 cycles consisting of planning, implementing actions, observing, and reflecting. The population in this study were all class XI students of SMAN 5 Palangka Raya. The sampling technique used was Purposive Sampling which is a method of determining samples that requires special consideration, and class XI was obtained as a sample in the study. Data collection techniques used tests and skills observation rubrics. The results of data analysis showed that the application of the Reciprocal Teaching Learning Model increased the average value of students' cognitive learning outcomes, from 70.00 with classical completeness of 53% in Cycle I to 84.29 with classical completeness of 93% in Cycle II. Thus it can be concluded that the application of the Reciprocal Teaching Learning Model can improve students' cognitive learning outcomes in the subject of Biology class XI SMAN 5 Palangka Raya.